The Collective Practice of Music. Youth Symphonic Band of San Pedro Sula: A Possible Space for Sustainable Social Development - Rodríguez-Reinoso, Oswaldo Antonio; Luna-Nemecio, Josemanuel (Revista Electrónica Educare, 2022)
Introduction. Music education, which combines disciplinary and social development purposes, represents an alternative that re-dimensions the teaching-learning of music from a collective doing. The Youth Symphonic Band of San Pedro Sula (BSJ-SPS) is a non-formal musical education program that experiences the collective practice of music as a space for sustainable social development. Purposes. To reveal the pedagogical, artistic, and socio-cultural aspects of this experience in the light of approaches to music education for social development. Method. The qualitative, quasi-experimental, and descriptive research used the testimonial narrative of eight (8) students of the BSJ-SPS collected in semi-structured interviews, analyzed through categorization and coding techniques. The analysis resulted in twelve emerging categories that frame the experience in the BSJ from the experience of its students, both pedagogically and artistically and socio-culturally. Conclusion. There is a clear link between disciplinary and social development purposes in the BSJ program. Its members experience a practice that they recognize as a factor of important personal transformation, strengthening their ethical life project.